Successful diuretics treatment of protein‐losing enteropathy in Noonan syndrome. Issue 2 (April 2015) - Mizuochi, Tatsuki; Suda, Kenji; Seki, Yoshitaka; Yanagi, Tadahiro; Yoshimoto, Hironaga; Kudo, Yoshiyuki; Iemura, Motofumi; Tanikawa, Ken; Matsuishi, Toyojiro
Abstract There are few reports on successful high‐dose spironolactone treatment of refractory protein‐losing enteropathy (PLE) caused by Fontan procedure. We report successful diuretics treatment with spironolactone and furosemide at standard dose, of refractory PLE in a patient with Noonan syndrome and repaired congenital heart disease. This is the first successful application of diuretics treatment in a patient with refractory PLE without Fontan procedure. This case illustrates that diuretics treatment can be the first‐line treatment of PLE regardless of the causative physiology, and can be effective in refractory PLE with Noonan syndrome.